2015
DOI: 10.1007/s00894-015-2708-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of interactions and pharmacophore development for DFG-out inhibitors to RET tyrosine kinase

Abstract: RET (rearranged during transfection) tyrosine kinase is a promising target for several human cancers. Abt-348, Birb-796, Motesanib and Sorafenib are DFG-out multi-kinase inhibitors that have been reported to inhibit RET activity with good IC50 values. Although the DFG-out conformation has attracted great interest in the design of type II inhibitors, the structural requirements for binding to the RET DFG-out conformation remains unclear. Herein, the DFG-out conformation of RET was determined by homology modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…For instance, IGF-1 is one of the key molecules in cancer biology, however, little is known about the role of the E peptide. The E peptide is thought to have functional properties as the release from IGF-1 is thought to induce cellular proliferation in the human prostate cancer (39). The C peptide of proinsulin is important in the processing of mature insulin and may have biological activity as a report suggests that it binds to a G protein-coupled surface receptor and activates Ca 2ϩ -dependent intracellular signaling pathways (40).…”
Section: Functions Of C Elegans Insulin Peptidesmentioning
confidence: 99%
“…For instance, IGF-1 is one of the key molecules in cancer biology, however, little is known about the role of the E peptide. The E peptide is thought to have functional properties as the release from IGF-1 is thought to induce cellular proliferation in the human prostate cancer (39). The C peptide of proinsulin is important in the processing of mature insulin and may have biological activity as a report suggests that it binds to a G protein-coupled surface receptor and activates Ca 2ϩ -dependent intracellular signaling pathways (40).…”
Section: Functions Of C Elegans Insulin Peptidesmentioning
confidence: 99%
“…The whole workflow of MD simulations was the same as that in those carried out in our previous studies. 28 , 29 , 39 A buffer distance of 10.0 Å was used to solvate the structures with TIP3P water in periodic boxes. To adjust the electroneutrality condition of the systems, 0.1 mol/L of Na + and Cl – ions were added.…”
Section: Methodsmentioning
confidence: 99%
“…The Eg5–PVZB1194 complex structure was retrieved from the protein databank (PDB ID: 3WPN). The default protein preparation wizard in Schrödinger was used to prepare and refine the structure in the same manner as in our previous studies. , First, the structure was checked to guarantee the chemical correctness. Hydrogens were added to the structure, and the side chains that were far from the binding pocket and not forming any salt bridges with other side chains were neutralized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMPBSA was widely applied in the development of anticancer compounds where kinases were identified as the most promising targets. Recent inhibitor design includes the epidermal growth factor receptor kinase domain (Li et al, 2015 ; Moonrin et al, 2015 ; Zhao et al, 2017 ), anaplastic lymphoma kinase (Kong et al, 2015 ), cyclin-dependent kinases (Li X. L. et al, 2014 ; Czelen, 2016 ; Dong et al, 2016a , b , 2017 ; Arba et al, 2017 ), extracellular signal-regulated kinase 2 (Chen, 2017 ), casein kinase 2 (Wang X. W. et al, 2014 ), sphingosine kinases (Fang et al, 2016 ), Src/Abl tyrosine kinases (Fong, 2015 ; Ma et al, 2015 ), RET tyrosine kinase (Gao et al, 2015 ), PRK1 (Slynko et al, 2014 ), Akt kinase (Lu et al, 2015 ), phosphatidylinositol 3 kinase (Bian et al, 2014 ), and Myt1 kinase (Wichapong et al, 2014 ). As an illustration of the method's performance, Slynko et al observed a correlation coefficient of 0.78 between the experimental pIC 50 of 26 PRK1 inhibitors and computational MMPBSA binding affinities.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%